INFERENSI KONTEKS BERDASARKAN ANALISIS RELASI MAKNA WEBTOON “SMILE BRUSH: MY OLD PICTURES” - Pehala, Ilfan Askul; Zur, Sarjaniah; Safei, Nur Hasanah (Sunan Kalijaga State Islamic University Yogyakarta, 2022)
The study in this research is oriented to the analysis and description of inferences on the context and a comprehensive understanding of other linguistic variables in the text and discourse in it. The research data are lingual lexical units and phrases that show the relation of synonymy and polysemy meanings in the narrative text of the comic